Evaluación de las inteligencias múltiples en estudiantes de la Institución Educativa Primaria N° 60001 Meneleo Meza López, Iquitos 2022 - Tamani Nolorve, Billy (2024)
The present study had the objective of evaluating the students of the Educational Institution Nº 60001 of the city of Iquitos, 2022. The research work is at the descriptive level of study and is of a direct quantitative nature. The population consisted of 325 primary school students, while the sample consisted of 176 students based on proportional distribution. The questionnaire served as an instrument and the survey technique was used. Statistical graphs were used to analyze the averages and percentages of the data tables. The most relevant conclusions of the analysis of the weighted mean component of the students' multiple intelligences are presented below: With a score of 39.4, naturalistic intelligence is the most developed, followed by intrapersonal intelligence with a score of 36.3, spatial intelligence with a score of 34.4, musical intelligence with an average of 32.3 and bodily-kinesthetic intelligence with an average of 31.2. The data collected were evaluated by means of statistical tables and graphs, the mean was applied, which made it possible to respond to the stated objectives.